JAZ8 Interacts With VirE3 Attenuating Agrobacterium Mediated Root Tumorigenesis - Li, Shijuan; Xu, Bingliang; Niu, Xiaolei; Lu, Xiang; Cheng, Jianping; Zhou, Meiliang; Hooykaas, Paul J. J. (Frontiers in Plant Science, 2021)
Agrobacterium tumefaciens can cause crown gall tumors by transferring both an oncogenic piece of DNA (T-DNA) and several effector proteins into a wide range of host plants. For the translocated effector VirE3 multiple functions have been reported. It acts as a transcription factor in the nucleus binding to the Arabidopsis thaliana pBrp TFIIB-like protein to activate the expression of VBF, an F-box protein involved in degradation of the VirE2 and VIP1 proteins, facilitating Agrobacterium-mediated transformation. Also VirE3 has been found at the plasma membrane, where it could interact with VirE2. Here, we identified AtJAZ8 in a yeast two-hybrid screening with VirE3 as a bait and confirmed the interaction by pull-down and bimolecular fluorescence complementation assays. We also found that the deletion of virE3 reduced Agrobacterium virulence in a root tumor assay. Overexpression of virE3 in Arabidopsis enhanced tumorigenesis, whereas overexpression of AtJAZ8 in Arabidopsis significantly decreased the numbers of tumors formed. Further experiments demonstrated that AtJAZ8 inhibited the activity of VirE3 as a plant transcriptional regulator, and overexpression of AtJAZ8 in Arabidopsis activated AtPR1 gene expression while it repressed the expression of AtPDF1.2. Conversely, overexpression of virE3 in Arabidopsis suppressed the expression of AtPR1 whereas activated the expression of AtPDF1.2. Our results proposed a novel mechanism of counter defense signaling pathways used by Agrobacterium, suggesting that VirE3 and JAZ8 may antagonistically modulate the salicylic acid/jasmonic acid (SA/JA)-mediated plant defense signaling response during Agrobacterium infection.